From governance contagion to risk contagion: research on systemic risk contagion from the perspective of governance externality - Jia, Kaiwei; Yin, Longhe (Frontiers in Physics, 2024)
The impact of financial institution governance on systemic risk is crucial and controversial. In view of the important role of fund shareholding in the corporate governance of financial institutions, this paper takes financial institutions in China as the research object, constructs the association network of financial institutions based on fund shareholding, and empirically examines the impact of fund shareholding in financial institutions on systemic risk. The results show that fund shareholding significantly increases the systemic risk of financial institutions through the network. Convergence in funds' choice of investment targets is an important mechanism for risk contagion among banks, insurance companies, securities companies, and across sectors. The governance externality created by fund holdings in financial institutions is thus corroborated. Further analysis shows the peer effect of funds' investment behaviour is an important cause of share price convergence and governance convergence of held financial institutions, while majority shareholder monitoring and information transparency can effectively curb systemic risk contagion from governance externality. The study confirms the proposition of corporate governance externality in financial institutions, enriches the formation mechanism of systemic risk contagion from the perspective of corporate governance, and provides a theoretical guideline for effectively curbing the systemic risk caused by governance externality.